Jesus in the Mist : Stories - Ruffin, Paul (Book collections on Project MUSE., 2007)
Remarkable stories of seekers, idealists, visionaries and the occasional racist, written in an authentic Southern idiom. Stubborn characters ... on a quest to understand their purpose dominate these stories. ... [R]ealistic pictures of social tensions of the time.